THE EFFECT OF DIGITAL MARKETING, BRAND AMBASSADORS, AND BRAND AWARENESS ON PURCHASE DECISIONS AT PT. MATAHARI DEPARTMENT STORE MANADO TOWN SQUARE - Muksin, Drivera; Pandowo, Merinda; Gunawan, Emilia (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2024)
This research aims to determine the effect of digital marketing, brand ambassador, and brand awareness on purchase decision at PT. Matahari Department Store Manado Town Square. This research will use causal type of research with Quantitative method. As an analysis tool this research will use multiple linear regression method. The population of this research is customer of People who has purchase from Matahari Department Store. Data will be collected by a questionnaire. The result of this research shows that digital marketing has a positive and significant effect on consumer purchase decision at PT. Matahari Department Store Manado Town Square, brand ambassador has a positive but not significant effect on consumer purchase decision, brand awareness has a positive and significant effect on consumer purchase decision at PT. Matahari Department Store Manado Town Square, and digital marketing, Brand ambassador, and Brand awareness, has a positive and significant effect simultaneously on consumer purchase decision at PT. Matahari Department Store Manado Town Square. This study recommended that PT. Matahari Department Store Manado Town Square should focus on maintaining digital marketing strategies and activities, and keep maintaining or improving brand awareness to improve and create purchase decision.   Keyword: Digital Marketing, Brand Ambassador, Brand Awareness, Purchase Decision